The Effect of Cloud Classroom (CCR) on Material Energy on Communication Skill and Learning Outcome Junior High School - Iwan Wicaksono; Indrawati Indrawati; Nia Erlina; Della Presilia (Universitas Lambung Mangkurat, 2022)
CCR is a virtual classroom that can be used for online learning and assessment. By learning to use CCR media can improve communication skills and learning outcomes. This study aims to examine the effect of using CCR on science material, especially energy, on communication skills and learning outcomes for seventh grade Junior High School students. This research is a quasi-experimental research with a post-test only control group design. The sample of this study was class VII B as the experimental class and class control class VII D. The research instrument used was a questionnaire sheet to measure communication skills and tests were used to measure learning outcomes. The data obtained were analyzed using statistical tests. The results of data analysis on communication skills were normally distributed, so that the independent sample t-test was continued to obtain a value that had a significant difference in the average score of the communication skills questionnaire of the experimental class and control class. Furthermore, the right-hand t-test was performed. The results of data analysis on learning outcomes were normally distributed so that the independent sample t-test continued to obtain a significant value for the average score of the student learning outcomes in the experimental class and the control class. Furthermore, the right-hand t-test was carried out. It can be concluded that CCR has an effect on communication skills and learning outcomes can be seen from the results of questionnaires, observations and the average score of learning outcomes.